Load versus displacement-controlled nanocompression: Insights from atomistic simulations. (15th March 2023) - Iteney, Hugo; Cornelius, Thomas W.; Thomas, Olivier; Amodeo, Jonathan
Abstract: The mechanics of nano-objects strongly depend on the experimental setup used. Indeed, experimental devices generate stress either by controlling the force exerted by the grips (or indenters) or by monitoring their displacements, while software-based feedback loops are also developed to control displacements using force actuators. Often, nanomechanical experiments are interpreted using intrinsically displacement-controlled molecular dynamics simulations, without questioning the influence of the control mode. In this study, we develop an original strategy to perform load-controlled molecular dynamics simulations applied here to nanoparticles under compression as a test-case. While displacement-controlled simulations show intermittent plasticity and load drops, load-controlled simulations are characterized by strain-bursts more in line with load-controlled experiments. Here, a special attention is paid to the dislocation microstructure evolution depending on the control mode. Finally, interpretations of recent experiments based on atomistic simulations are revised, including the envelope load model usually used to correlate displacement-controlled atomistic simulations and load-controlled experiments at small-scales. Graphical abstract: